2023
DOI: 10.1039/d3ta03447j
|View full text |Cite
|
Sign up to set email alerts
|

In-depth understanding the temperature-dependent reversible phase transition in CsPbI3−xBrx perovskites and its associated photophysical properties

Songyang Yuan,
Jiahuan Deng,
Hui Xiong
et al.

Abstract: Although all-inorganic CsPbI3-xBrx (0 ≤ x ≤ 3) perovskites display largely potential toward the photoelectric applications, in-depth understanding the origin of phase transition and its associated photophysical properties are still...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Meanwhile, the iodine ions affect the chemical environment of the bromide ions that may result from their noncovalent interaction, and the augmented interactions are favorable for the phase stability of CsPb(Br 1−x I x ) 3 QDs. 46,47 Consequently, the carrier transport process becomes more dependable, and the CsPb(Br 1−x I x ) 3 QD-based devices are expected to deliver a higher stability. To further understand the carrier transport properties and resistive switching mechanism of CsPb(Br 1−x I x ) 3 QD-based devices, we redrew the I−V curves on a double-logarithmic scale.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the iodine ions affect the chemical environment of the bromide ions that may result from their noncovalent interaction, and the augmented interactions are favorable for the phase stability of CsPb(Br 1−x I x ) 3 QDs. 46,47 Consequently, the carrier transport process becomes more dependable, and the CsPb(Br 1−x I x ) 3 QD-based devices are expected to deliver a higher stability. To further understand the carrier transport properties and resistive switching mechanism of CsPb(Br 1−x I x ) 3 QD-based devices, we redrew the I−V curves on a double-logarithmic scale.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It is suggested that iodine ion doping mainly affects the chemical environment of the [PbX 6 ] 4– octahedron and advances the covalent interactions between lead ions and halide ions. Meanwhile, the iodine ions affect the chemical environment of the bromide ions that may result from their noncovalent interaction, and the augmented interactions are favorable for the phase stability of CsPb­(Br 1– x I x ) 3 QDs. , Consequently, the carrier transport process becomes more dependable, and the CsPb­(Br 1– x I x ) 3 QD-based devices are expected to deliver a higher stability.…”
Section: Resultsmentioning
confidence: 99%
“…LHPs are compounds with the chemical formula ABX 3 , where the A-site cation is commonly formamidinium (FA + ), and/or cesium (Cs + ); the B-site cation is lead (Pb 2+ ); and the X-site anion is iodine (I – ) and/or bromine (Br – ). , LHPs are characterized by corner-sharing PbX 6 octahedra and some degree of defect tolerance that lead to long-lived charge carriers. However, these corner-sharing octahedra are not always thermodynamically phase stable at room temperature. Inorganic CsPbI 3 goes through an undesirable phase transformation from the cubic (α) phase to the orthorhombic Pnma (δ) phase below 325 °C . FAPbI 3 spontaneously transforms from the cubic (α) phase to the undesirable hexagonal phases (2H-, 4H-, and 6H-FAPbI 3 ) , below 150 °C .…”
Section: Introductionmentioning
confidence: 99%
“…22−24 Inorganic CsPbI 3 goes through an undesirable phase transformation from the cubic (α) phase to the orthorhombic Pnma (δ) phase below 325 °C. 25 FAPbI 3 spontaneously transforms from the cubic (α) phase to the undesirable hexagonal phases (2H-, 4H-, and 6H-FAPbI 3 ) 26,27 below 150 °C. 28 Thermal instability is currently remediated by mixing both Cs and FA cations, 24 with single crystals of Cs 0.1 FA 0.9 PbI 3 showing a stable cubic phase at as low as 27 °C.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation